Fertility preservation counselling in Dutch Oncology Practice: Are nurses ready to assist physicians?. (27th December 2016) - Krouwel, E.M.; Nicolai, M.P.J.; van Steijn‐van Tol, A.Q.M.J.; Putter, H.; Osanto, S.; Pelger, R.C.M.; Elzevier, H.W.
Abstract : Cancer and its treatments may result in impaired fertility, which could cause long‐term distress to cancer survivors. For eligible patients, fertility preservation (FP) is available to secure future reproductive potential. Many physicians, however, feel inhibited about discussing FP. Oncology nurses may serve as an initiator for discussing the subject and provide additional support. Our aim was to investigate their knowledge about FP, the way they apply this, and possible barriers to discussing FP with patients of reproductive age. A questionnaire was administered via mail, Internet and the Dutch Oncology Nursing Congress. Four hundred and twenty‐one oncology nurses participated, a third of whom (31.1%) had "sufficient" knowledge of FP. Twenty‐eight per cent of participants reported that they "never/hardly ever" discussed FP; 32.2% "almost always/always." FP discussions were more frequently performed by graduate nurses, academic nurses, experienced nurses and nurses with sufficient knowledge. Reasons for not discussing FP were a "lack of knowledge" (25.2%), "poor prognosis" (16.4%) and "lack of time" (10.5%). In conclusion, several obstacles may result in FP not being routinely discussed, specifically a lack of knowledge. Yet nurses feel responsible for addressing the issue, indicating that assistance with FP discussions should be encouraged. Educational training about FP is recommended.